Quality performance of Mara University of Technology Samarahan Campus (UiTMCSKS) 2001 / Iris Syawe Seh Ling … [et.al.]. - Iris Syawe, Seh Ling; Hamali, Jamil; Nee' Gaik, Mary Gunjew; Duncan, William; Ho Boon, Heong (2002)
In the first three-quarter of the last century, higher education was mostly reserved for the elite, who should study the theoretical aspects of concepts, preferably from textbooks in order to later serve the needs of industry and technology. The quality of students was guaranteed by the strict assessments that they went through at the primary and secondary levels. However, there was a shift from this traditional elitist system of higher education to a 'mass system in the last three decades in countries like the United Kingdom and North America and for Malaysia in the last decade. The accelerated demand for higher education had triggered the mushrooming of institutions of higher learning from 44 in 1991 to currently 676 (Education Guide 7th Edition, 2000) all bent on providing varieties of field of studies. Since, the education business is a lucrative one, competition from the providers had lowered entry requirements.